The Business Model Canvas "Camelina omega 3 Plus" - Ion Toncea; Mihai Iordache (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The Business Model Canvas "Camelina omega 3 Plus" is a transpose in practice of the information from the best seller book "Business Model Generation - A handbook for Visionaries, Game Changers and Challengers" written by the Alexander OSTERWALDER & Yves PIGNEUR and of the knowledge accumulated from the complex and diverse activities carried on during project H2020 - EU RUR-09-2017 'Replicable business models for modern rural economies (RUBIZMO), financed under Grant Agreement No 773621, in which the Business Model Canvas is a basic tool. Firstly, the paper is focusing on a clear presentation of the structural elements (9) of the business model canvas - (PC) Key partners and partnerships, (AC) Key activities, (R-C) Key resources, (PV) Value propositions, (CA) Channels, (RC) Customer relationships, (SC) Customer segments, (C) Costs structure and (FV) Revenue Streams. Further on it is presented the description, analysis and design of the Business Model Canvas "Camelina Omega 3 Plus", a case study for inspiration of those who are interested to develop or who are already running a sustainable business based on similar values as the company "Camelina Omega 3 Plus".
Keywords: O31; 330; business; model; canvas; camelina; omega 3